The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.11591/edulearn.v16i2.20496
|View full text |Cite
|
Sign up to set email alerts
|

Students’ preferences and challenges in learning English fully online with Google Classroom

Abstract: The Coronavirus 2019 outbreak caused the world to experience a pandemic and paralyze human activities, including the education sector. Consequently, the teaching-learning system changed from face-to-face to online. This study aimed to determine how high school students' preferences and challenges in Pekanbaru city employing the Google Classroom to learn English. This descriptive study involved 30 high school and vocational high school students as the sample who obtained through purposive sample technique. Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…he relationship between teachers and students runs smoothly while using the Google Classroom application, as well as the assignments are given to students by the instructor, and they feel helped by the reminder, which is one of the features in the Google Classroom application. Furthermore, the reminder features of the Google Classroom application help students recall the deadlines for assignments that they must complete and apply (Wahyuni et al, 2022). It means that the result supported the theory proposed by Ferdianto and Dwiniasih (2019) who stated that this learning management system provides excellent commenting system.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…he relationship between teachers and students runs smoothly while using the Google Classroom application, as well as the assignments are given to students by the instructor, and they feel helped by the reminder, which is one of the features in the Google Classroom application. Furthermore, the reminder features of the Google Classroom application help students recall the deadlines for assignments that they must complete and apply (Wahyuni et al, 2022). It means that the result supported the theory proposed by Ferdianto and Dwiniasih (2019) who stated that this learning management system provides excellent commenting system.…”
Section: Resultssupporting
confidence: 75%
“…Santos (2021) supports that compared to traditional setting, learning when supported with google classroom offers effective real-time interaction between students and teachers and support many kinds of learning assessment. A more recent study conducted by Wahyuni et al, (2022) found that Google Classroom has been used to support online learning during Covid-19 pandemic and offers flexibility of learning.…”
Section: Introductionmentioning
confidence: 99%
“…The students did not agree that the use of Google Classroom could replace the full role of the teacher in the classroom. Google Classroom is only an online learning medium to help students learn, especially during this Covid-19 pandemic (Wahyuni et al, 2022). The material will be easier to understand when there is direct communication between the teacher and students in the classroom (Parmawan et al, 2022).…”
Section: Series1mentioning
confidence: 99%
“…Therefore, in groups students will give each other opinions or independent presentations and during performance in groups each student will improve each other so that every grammar will be correct, also each student's vocabulary will increase with each other with a lot of listening. PBL is an instructional approach that contextualizes learning by presenting students with problems to solve to develop (Syakur et al, 2020) PBL is different from traditional learning which emphasizes learning through studentcentered, interdisciplinary, and integrated activities in real-world situations (Wahyuni et al, 2022). More importantly, PBL is process oriented.…”
Section: Introductionmentioning
confidence: 99%